MANIPULASI TEGANGAN LISTRIK PADA SALINITAS YANG BERBEDA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN KERLING (Tor tambroides) - Farah Diana (Universitas Teuku Umar, 2015)
Tor tambroides (local name is kerling) is one of commercial fish espicially in Aceh, West Java, and North Sumatra. Salinity and electrical conductivity is known can affecting to fish physiologi. Purpose of this study is to knowing survival rate and growth rate of Tor tambroides juvenile, with different salinity and electrical conductivity as treatment. Survival rate, daily growth rate, absolute length growth and biomass growth rate was used as variable test. Result of study show that electrical conductivity with different salinty (0,3,5,7 ppt) (during 30 days) unaffecting to daily growth rate and biomass growth rate. However, manipulation of electrical conductivity with different salinity have been affecting to absolute length growth and survival rate. The range of value for survival rate is ±83,33 – 100%, daily growth rate is ±0,40 – 0,71%, absolute length growth is ±1,30 – 2,27% and the range of value for biomass growth rate is ±0,102 – 0,183 gram.